Characterization of a high oleic oil extracted from papaya (Carica papaya L.) seeds - Malacrida, Cassia Roberta [UNESP]; Kimura, Mieko [UNESP]; Jorge, Neuza [UNESP] (Soc Brasileira Ciência Tecnologia Alimentos, 2011)
The physicochemical characteristics, fatty acid, tocopherol, and carotenoid composition of a crude oil extracted from papaya (Carica papaya L.) seeds, formosa variety, were investigated. The oil yield from the seeds was 29.16%. The data obtained for the analytical indexes were in agreement with those of other edible oils. The oil obtained had high oxidation resistance (77.97 hours). The major fatty acids in total lipid were oleic (71.30%), palmitic (16.16%), linoleic (6.06%), and stearic (4.73%) acid. The alpha and delta-tocopherol were the predominant tocopherols with 51.85 and 18.89 mg.kg(-1), respectivelly. The beta-cryptoxanthin (4.29 mg.kg(-1)) and beta-carotene (2.76 mg.kg(-1)) were the carotenoids quantified, and the content of total phenolic compounds was 957.60 mg.kg(-1). Therefore, the potential utilization of the papaya seeds for oil production seems favorable. However, toxicological studies need to be carried out before the oil is appropriate for food applications.
Caracterização de um óleo alto oleico extraído de sementes de mamão (Carica papaya L.)
Keywords: seed oil; fatty acid; Tocopherol; carotenoid; total phenolics